2020
DOI: 10.1093/jn/nxaa289
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Features and Excess Weight Were Inversely Associated with Nut Consumption after 1-Year Follow-Up in the PREDIMED-Plus Study

Abstract: Background High nut consumption has been previously associated with decreased prevalence of metabolic syndrome (MetS) regardless of race and dietary patterns. Objectives The aim of this study was to assess whether changes in nut consumption over a 1-y follow-up are associated with changes in features of MetS in a middle-aged and older Spanish population at high cardiovascular disease risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
4
28
0
1
Order By: Relevance
“…However, it is worth noting that only those studies conducted in people with overweight and obesity showed significant percentage reductions in both nut and control groups for BW, WC, and BMI (only nut groups), and that such differences were only significant with longer follow-up periods (>12 weeks). These results agreed with previous evidence in PREDIMED trials in a wide range of subjects that showed that nut consumption had an inverse association with excess weight and metabolic syndrome [ 144 ]. Although we have to interpret this with caution, the clinical message seems to be that nut consumption does not lead to a weight or adiposity increase in healthy/normal weight people or people with overweight/obesity.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is worth noting that only those studies conducted in people with overweight and obesity showed significant percentage reductions in both nut and control groups for BW, WC, and BMI (only nut groups), and that such differences were only significant with longer follow-up periods (>12 weeks). These results agreed with previous evidence in PREDIMED trials in a wide range of subjects that showed that nut consumption had an inverse association with excess weight and metabolic syndrome [ 144 ]. Although we have to interpret this with caution, the clinical message seems to be that nut consumption does not lead to a weight or adiposity increase in healthy/normal weight people or people with overweight/obesity.…”
Section: Discussionsupporting
confidence: 92%
“…The high content of antioxidants, polyphenols and fiber found in MD have been previously associated with decreased systemic inflammation and central obesity, which could explain its beneficial effect [ 112 , 113 ]. Moreover, an enhanced with nuts MD was found to be helpful regarding the maintenance of body weight status [ 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 13 articles were critically appraised using Critical Appraisal Skills Programme (CASP) and Joanna Briggs as appropriate and are reported in Appendix A and are present in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). This integrative review included studies with various methodologies, including five randomized control trials (Blackford et al, 2016;Chirinos et al, 2016;Ramos et al, 2016;Seward et al, 2019;Ying et al, 2016), one quasi-experimental reversal design (Guadalupe-Grau et al, 2018), one randomized cross over study (Hald et al, 2016), two prospective longitudinal studies (Jeejeebhoy et al, 2017;Julibert et al, 2020), one qualitative content analysis of individual interviews (Joelsson et al, 2020), one causal model test (Lee et al, 2016), one randomized parallel controlled single center design (Ruscica et al, 2018), and one prospective randomized double blind placebo controlled clinical study (Usharani et al, 2019).…”
Section: Identifying the Problem And Developing A Literature Search Questionmentioning
confidence: 99%
“…There were a range of dietary interventions found in the articles of this review that were used as a component to the management of MetS. The most common dietary suggestions to offer patients in the management of MetS discussed included, increasing dietary fibre, vegetable, fruit, and healthy fat intake Eight of the thirteen articles addressed some form of dietary intervention to manage metabolic syndrome, however only four studies looked exclusively at a dietary component (Hald et al, 2016;Julibert et al, 2020;Ruscica et al, 2018;and Usharani et al, 2019). Hald et al (2016) examined the effect of increased dietary fibre on body weight and gut microbiome.…”
Section: Dietary Interventionmentioning
confidence: 99%
See 1 more Smart Citation